Analysis on phase distribution and flow field morphology in double side blown gas-liquid mixture flows with high temperature and high density melt - Wu, Xudong; Wang, Shibo; Hu, Jianhang; Wang, Hua; Xiao, Qingtai; Deng, Ge; Li, Dongbo (Frontiers in Energy Research, 2023)
In view of the gas-liquid two-phase flow process in the oxygen-enriched side-blown molten pool, the phase distribution and manifold evolution in the side-blown furnace under different working conditions are studied. Based on the hydrodynamics characteristics in the side-blown furnace, a multiphase interface mechanism model of copper oxygen-enriched side-blown bath melting was established. The results show that the existence of slag baffle makes the velocity distribution range of melting mixing zone wider, the mixing range of melt wider, the mixing effect better, and the role of melting zone strengthened. The average speed of case MY in the melting zone is the highest, nearly 5.2% higher than that of case EY, and 16.7% higher than that of case EN. Compared with the average turbulent kinetic energy in the melting zone, case MY has a significant advantage of 2.635 m2/s2, which is increased by 47%, 34% and 14% respectively compared with case EN, case EY and case MN.